2013 IEEE Workshop on Applications of Signal Processing to Audio and Acoustics 2013
DOI: 10.1109/waspaa.2013.6701816
|View full text |Cite
|
Sign up to set email alerts
|

Virtual autoencoder based recommendation system for individualizing head-related transfer functions

Abstract: We propose a virtual autoencoder based recommendation system for learning a user's Head-related Transfer Functions (HRTFs) without subjecting a listener to impulse response or anthropometric measurements. Autoencoder neural-networks generalize principal component analysis (PCA) and learn non-linear feature spaces that supports both out-of-sample embedding and reconstruction; this may be applied to developing a more expressive low-dimensional HRTF representation. One application is to individualize HRTFs by tun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…This last set of experiments is based on the notion that autoencoders perform a similar task as PCA, while also learning non-linear feature spaces [16]. Accordingly we found that, with as little as 20 principal components, it is possible to reconstruct HRTFs with an average SD of 1.7 dB -see Fig.…”
Section: Pca-based Hrtf Predictionmentioning
confidence: 69%
“…This last set of experiments is based on the notion that autoencoders perform a similar task as PCA, while also learning non-linear feature spaces [16]. Accordingly we found that, with as little as 20 principal components, it is possible to reconstruct HRTFs with an average SD of 1.7 dB -see Fig.…”
Section: Pca-based Hrtf Predictionmentioning
confidence: 69%
“…Many different algorithms have been developed for binaural sound localization including simple regression models like SVR [14], GPR [28], and deep neural network models [46]. In this paper, we follow a state-of-the art neural network-based model in [46], to evaluate the benefits of accurate HRTF predictions.…”
Section: Binaural Localizationmentioning
confidence: 99%
“…Several individualization methods involving DL technologies have also been proposed. Luo et al [17] trained a stacked denoising autoencoder to encode and reconstruct HRTFs from multiple subjects. The resulting latent representation is then manipulated using feedback from the user to optimize their localization performances.…”
Section: Related Workmentioning
confidence: 99%